Inter-departmental correspondence - Gillies, William
030-0152-001 Inter-Departmental Correspondence. THE LABOUR PARTY To avoid unnecessary delay, please use this form when a communication is received bearing on subjects additional to those appertaining to your department. Subject (ONE SUBJECT ONLY). From (Name of Organisation) Signature Address Date Particulars The following is an excerpt from a letter from Mrs. Barbara Wood, of the National Joint Committee for Spanish Relief, Valencia, June 13, 1938: "I am still getting urgent requests for soap, especially from the South of Spain, where the problem of hygiene is particularly acute at this season. Refugees themselves have said to me that they would willingly go without food if only they could have soap to keep themselves clean." Handed from...............Mr.Gillies....................................... To..............Mr. Tewson Date................ June.....20, 1938 292/946/30/152